Original quantitative research - Examining the municipal-level representativeness of the Canadian Longitudinal Study on Aging (CLSA) cohort: an analysis using Calgary participant baseline data - Norberg, Samantha J. (Health Promot Chronic Dis Prev Can, 2021)
INTRODUCTION: The Canadian Longitudinal Study on Aging (CLSA) is a rich, nationally representative population-based resource that can be used for multiple purposes. Although municipalities may wish to use CLSA data to address local policy needs, how well localized CLSA cohorts reflect municipal populations is unknown. Because Calgary, Alberta, is home to one of 11 CLSA data collection sites, our objective was to explore how well the Calgary CLSA sample represented the general Calgary population on select sociodemographic variables. METHODS: Baseline characteristics (i.e. sex, marital status, ethnicity, education, retirement status, income, immigration, internal migration) of CLSA participants who visited the Calgary data collection site between 2011 and 2015 were compared to analogous profiles derived from the 2011 National Household Survey (NHS) and 2016 Census datasets, which spanned the years when data were collected on the CLSA participants. RESULTS: Calgary CLSA participants were representative of the Calgary population for age, sex and Indigenous identity. Discrepancies of over 5% with the NHS and/or 2016 Census were found for marital status, measures of ethnic diversity (i.e. immigrant status, place of birth, non-official language spoken at home), internal migration, income, retirement status and education. CONCLUSION: Voluntary studies face challenges in recruiting fully representative cohorts. Communities opting to use CLSA data at a municipal level, including the 10 other CLSA data collection sites, should exercise caution when interpreting the results of these analyses, as CLSA participants may not be fully representative of the local population on select characteristics of interest.